ENHANCING PROFESSIONAL COMPETENCE THROUGH INTEGRATED EDUCATION AND INDEPENDENT LEARNING IN HIGHER EDUCATION (Web of Teachers: Inderscience Research, 2025)
The future development of a country is largely determined by the quality of its education system, particularly the higher education sector, which plays a pivotal role in preparing highly qualified professionals. With a focus on the reform of the education system, this study emphasizes the importance of aligning educational training with labor market demands, improving both theoretical and practical knowledge in specialized disciplines, and enhancing the effectiveness of students' independent learning. The integration of education, science, and production is vital for the effective development of students' professional competencies. This paper discusses how interdisciplinary integration in independent learning fosters the practical and theoretical growth of students, improving their ability to apply knowledge in future professional activities. The research highlights the critical role of developing integrated learning tasks that encourage students’ self-education, ultimately enhancing their competencies. By exploring different levels of integrated learning—ranging from basic interdisciplinary connections to the creation of new interdisciplinary disciplines—this study demonstrates how these educational strategies contribute to the formation of well-rounded, qualified specialists. The results of this study underscore the necessity of independent learning in higher education for fostering professional competence, suggesting that the transition to integrated education is essential for producing skilled professionals across various fields.